The Role of Relational Capital in the Relationship between Human Capital and Financial Performance - Sumiati Sumiati; Risna Wijayanti; Hanifa Bennu Nur (AIBPM Publisher, 2022)
The presence of increasingly fierce competition in the industrial era 4.0 necessitates companies having high and rapid innovation capabilities that can maintain and spur competitiveness. Human capital has been identified as a source of competitive advantage as well as a critical success factor in improving firm performance (Wright and McMahan, 1992; Hall, 1993; Pfeffer, 1994). However, human capital consists not only of the ability to share, combine, and transfer knowledge, but also of the ability to network with various related parties in order to form cross-functional teams. The goal of this research is to discover the relationship between human capital and firm financial performance as mediated by relational capital. The sample for this study consists of 80 manufacturing companies listed on the Indonesia Stock Exchange. Multiple regression analysis was used in this study as an analytical technique. Human capital has no effect on financial performance, and relational capital does not significantly mediate the relationship between human capital and financial performance, according to the findings. The insignificant effect of relational capital could be explained by the availability of information about the company's environment that has not been used optimally to build relational capital in order to improve company performance